The Application Effect of Jiawei Sanyu Shengjing Decoction Combined with High Ligation of the Spermatic Vein in Varicocele Male Infertility Patients - Xiangpeng Lu; Hao Han; Zhi Biao Zhang; Hao Chen; Xingru Huang; Rui Zhang (Applied Bionics and Biomechanics)
Objective. To analyze the application effect of Jiawei Sanyu Shengjing decoction combined with high ligation of the internal spermatic vein in male infertility patients with varicocele (VC). Methods. 106 male infertility patients with VC treated in our hospital from December 2018 to March 2019 were selected as examples. According to the length of stay, they were divided into the control group and observation group, with 53 cases in each group. High ligation of the internal spermatic vein was performed in both groups. On this basis, the observation group was treated with modified Sanyu Shengjing decoction, and the therapeutic effects of the two groups were compared. Results. The effective rate of 94.34% in the observation group was higher than 79.25% in the control group (P<0.05). After treatment, the serum index level and sperm deformity rate in the observation group were lower than those in the control group, and the semen density and sperm activity were higher than those in the control group (P<0.05). Conclusion. The treatment of VC male infertility with modified Sanyu Shengjing decoction combined with high ligation of the internal spermatic vein can effectively improve the number of sperm and reduce the density of semen.